Life Habits and Mental Health: Behavioural Addiction, Health Benefits of Daily Habits, and the Reward System - Fujiwara, Hironobu; Tsurumi, Kosuke; Shibata, Mami; Kobayashi, Kei; Miyagi, Takashi; Ueno, Tsukasa; Oishi, Naoya; Murai, Toshiya (Frontiers in Psychiatry, 2022)
In this review, the underlying mechanisms of health benefits and the risk of habitual behaviours such as internet use and media multitasking were explored, considering their associations with the reward/motivation system. The review highlights that several routines that are beneficial when undertaken normally may evolve in excessive behaviour and have a negative impact. This is especially critical in the current era, where technology like the internet has become mainstream despite the enormous addictive risk. The understanding of underlying mechanisms of behavioural addiction and optimal level of habitual behaviours for mental health benefits are deepened by shedding light on some findings of neuroimaging studies, so as to facilitate better management and prevention strategies of addictive problems. With the evolution of the world, and the inevitable use of some technologies that carry the risk of addiction, more effective strategies for preventing and managing addiction are in more demand than before, and the insights of this study are also valuable foundations for future research.